What happens when donors pull out? Examining differences in motivation between health workers who recently had Performance-Based Financing (PBF) withdrawn with workers who never received PBF in the Democratic Republic of Congo - Maini, Rishma; Lohmann, Julia (International journal of health policy and management, 2019)
Background: A motivated workforce is necessary to ensure the delivery of high quality health services. In developing countries, performance-based financing (PBF) is often employed to increase motivation by providing financial incentives linked to performance. However, given PBF schemes are usually funded by donors, their long-term financing is not always assured, and the effects of withdrawing PBF on motivation are largely unknown. This cross-sectional study aimed to identify differences in motivation between workers who recently had donor-funded PBF withdrawn, with workers who had not received PBF. Methods: Quantitative data were collected from 485 health workers in 5 provinces using a structured survey containing questions on motivation which were based on an established motivation framework. Confirmatory factor analysis was used to verify dimensions of motivation, and multiple regression to assess differences in motivation scores between workers who had previously received PBF and those who never had. Qualitative interviews were also carried out in Kasai Occidental province with 16 nurses who had previously or never received PBF. Results: The results indicated that workers in facilities where PBF had been removed scored significantly lower on most dimensions of motivation compared to workers who had never received PBF. The removal of the PBF scheme was blamed for an exodus of staff due to the dramatic reduction in income, and negatively impacted on relationships between staff and the local community. Conclusion: Donors and governments unable to sustain PBF or other donor-payments should have clear exit strategies and institute measures to mitigate any adverse effects on motivation following withdrawal.
Gesehen am 24.10.2019